Can we predict tuberculosis cure? What tools are available?. Issue 5 (8th November 2018) - Goletti, Delia; Lindestam Arlehamn, Cecilia S.; Scriba, Thomas J.; Anthony, Richard; Cirillo, Daniela Maria; Alonzi, Tonino; Denkinger, Claudia M.; Cobelens, Frank
Antibiotic treatment of tuberculosis takes ≥6 months, putting a major burden on patients and health systems in large parts of the world. Treatment beyond 2 months is needed to prevent tuberculosis relapse by clearing remaining, drug-tolerant Mycobacterium tuberculosis bacilli. However, the majority of patients treated for only 2–3 months will cure without relapse and do not need prolonged treatment. Assays that can identify these patients at an early stage of treatment may significantly help reduce the treatment burden, while a test to identify those patients who will fail treatment may help target host-directed therapies. In this review we summarise the state of the art with regard to discovery of biomarkers that predict relapse-free cure for pulmonary tuberculosis. Positron emission tomography/computed tomography scanning to measure pulmonary inflammation enhances our understanding of "cure". Several microbiological and immunological markers seem promising; however, they still need a formal validation. In parallel, new research strategies are needed to generate reliable tests. In this review we summarise the state of the art with regard to discovery of biomarkers that predict relapse-free cure for pulmonary tuberculosis http://ow.ly/tR3430m2NVQ